Effect of ancient wheat pasta on gut microbiota composition and bacteria-derived metabolites: A randomized controlled trial - Baldi, Simone; Dinu, Monica; Pagliai, Giuditta; Colombini, Barbara; Di Gloria, Leandro; Curini, Lavinia; Pallecchi, Marco; Ramazzotti, Matteo; Bartolucci, Gianluca; Benedettelli, Stefano; Amedei, Amedeo; Sofi, Francesco (Frontiers in Nutrition, 2022)
Background and aim: In recent years, many studies have suggested that ancient wheat products might have beneficial effects on cardiometabolic risk profile, but little is known about their effect on gut microbiota (GM). The aim of the present study was to evaluate whether a replacement diet with pasta made from ancient wheat (AD) could influence the GM composition and its metabolites’ production compared to a replacement diet with pasta made from modern wheat (CD). Methods: A randomized, double-blinded crossover trial with two intervention phases was conducted on 20 clinically healthy adults (9 females; 11 males; mean age 43.1 ± 12.5 years). Study participants were assigned to consume pasta made using semi-whole flour from organic wheat that was either from ancient or modern control wheat for 8 weeks in a random order. An 8-week washout period was implemented between the interventions. Stool samples were collected from all subjects at the beginning and at the end of each intervention period. GM composition, and short- (SCFAs) and medium- chain fatty acids (MCFAs) production was evaluated. Results: Dietary interventions did not produce significant diversity in the GM composition at higher ranks (phylum and above), but only at genus level. In detail, the AD significantly (adj. p<0.05) changed the abundance of Erysipelatoclostridium spp., Bacteroides_pectinophilus_group spp., CAG-873 spp. and Holdemanella spp. The CD significantly affected the abundance of Akkermansia spp., CAG-873 spp., Hungatella spp., Lachnospiraceae_UCG-008 spp., NK4A214_group spp., Frisingicoccus spp., Megasphaera spp., Synergistes spp. and Tyzzerella spp. Regarding the production of SCFAs and MCFAs, AD resulted in a significant increase of faecal acetic (+0.7%), isobutyric (+30.1%), 2-methylbutyric (+64.2%), and isovaleric (+22.5%) acids. On the other hand, CD resulted in increased levels of isobutyric (+71.4%), 2-methylbutyric (+116.2%), isovaleric (+99%), and valeric (+21.4%) acids, and a reduction of butyric (-31.6%) and hexanoic (-66.4%) acids. Conclusions: A short-term replacement diet with both ancient and modern wheat pasta determined significant changes in GM composition at the genus level but notably the AD resulted in a greater beneficial impact on anti-inflammatory SCFAs.